2018
DOI: 10.1002/jum.14724
|View full text |Cite
|
Sign up to set email alerts
|

Formulating a Treatment Plan in Suspected Lymphoma: Ultrasound‐Guided Core Needle Biopsy Versus Core Needle Biopsy and Fine‐Needle Aspiration of Peripheral Lymph Nodes

Abstract: In cases of suspected lymphoma, CNB without FNA was sufficient to obtain an actionable diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
14
0
3
Order By: Relevance
“…All biopsy samples with suspicious lymphoid infiltrates were reviewed by hematopathologists, and a final diagnosis was achieved through integration of histopathology, immunohistochemistry, and flow cytometry and/or molecular studies. The utility of CNB was judged by whether it yielded an actionable diagnosis, allowing for either initiation of treatment or final determination of benignity requiring no further intervention (6).…”
Section: Methodsmentioning
confidence: 99%
“…All biopsy samples with suspicious lymphoid infiltrates were reviewed by hematopathologists, and a final diagnosis was achieved through integration of histopathology, immunohistochemistry, and flow cytometry and/or molecular studies. The utility of CNB was judged by whether it yielded an actionable diagnosis, allowing for either initiation of treatment or final determination of benignity requiring no further intervention (6).…”
Section: Methodsmentioning
confidence: 99%
“…17 A spring-loaded side notch or hollow-bore needle to obtain a solid core of tissue from the target lesion is F I G U R E 4 A-E, Forest plot on accuracy of CNB for lymphoma diagnosis-divided by lymphoma subtypes applied. 28 For best diagnostic results, the operator should perform several passes with a large bore needle and avoid necrotic areas. 8,29 The diagnostic yield is also affected by the operator's expertise and experience.…”
Section: Discussionmentioning
confidence: 99%
“…CNB has now become popular as a diagnostic tool for suspected lymphoma presenting in the head and neck 17 . A spring‐loaded side notch or hollow‐bore needle to obtain a solid core of tissue from the target lesion is applied 28 . For best diagnostic results, the operator should perform several passes with a large bore needle and avoid necrotic areas 8,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an international committee of cytopathologists proposed guidelines for standardizing the evaluation of lymph nodes by FNA cytopathology [1]. Prior studies have shown that FNA in conjunction with CNB help categorize lymph node specimens with actionable diagnoses in 67–100% of cases, allowing initiation of treatment or a definitive determination of benign etiology that requires no further intervention [2, 3]. While FNA is a helpful tool to rule-in or rule-out lymphoma, these studies have noted that FNA still shows limitations in accurate subclassification of lymphomas.…”
Section: Introductionmentioning
confidence: 99%